2013
DOI: 10.1002/cncr.28446
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends and predictors of salvage cancer treatment after failure following radical prostatectomy or radiation therapy: An analysis from the CaPSURE registry

Abstract: BACKGROUND Prostate cancer treatment after failure of primary therapy by either radical prostatectomy or radiation therapy can vary greatly. This study sought to determine trends and predictors of salvage treatment after failure of primary treatment in a community cohort over the past 10 years. METHODS From the community‐based Cancer of the Prostate Strategic Urologic Research Endeavor (CaPSURE) database, 6275 patients were identified who initiated a form of primary treatment for prostate cancer; 839 of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 29 publications
1
21
0
1
Order By: Relevance
“…The treatment failure rate found in the current study is in line with or slightly higher than findings of others in comparable patient populations [8,9,10]. Our definition comprises disease progression as measured by PSA levels with a threshold from Dutch guideline [6] (>0.2 ng/ml twice), as well as disease progression according to the urologist solely based on PSA levels, which has been done previously [11]. Most studies however have limited their outcome definition to BCR, although this is ambiguous since the employed threshold of PSA levels is diverse.…”
Section: Discussionsupporting
confidence: 70%
“…The treatment failure rate found in the current study is in line with or slightly higher than findings of others in comparable patient populations [8,9,10]. Our definition comprises disease progression as measured by PSA levels with a threshold from Dutch guideline [6] (>0.2 ng/ml twice), as well as disease progression according to the urologist solely based on PSA levels, which has been done previously [11]. Most studies however have limited their outcome definition to BCR, although this is ambiguous since the employed threshold of PSA levels is diverse.…”
Section: Discussionsupporting
confidence: 70%
“…The lack of consensus relates to the type of ST—radiation therapy (RT), hormone therapy (HT), or both—to the timing of treatment, and to the selection of cases most likely to benefit. Not all PSA-R patients elect ST: a recent study of the community-based Cancer of the Prostate Strategic Urologic Research Endeavor (CaPSURE) database found that approximately 36% of patients received no ST [4]. Further, timing of ST relative to PSA-R varies across patients.…”
Section: Introductionmentioning
confidence: 99%
“…[1234] While the overall utilization of potentially curative local salvage therapies after failure of primary therapy has increased in recent years, this trend has been exclusive of salvage radical prostatectomy (SRP), which is still rarely performed despite evidence of improved safety and oncologic efficacy in modern series. [567] Furthermore, it has been shown that a high proportion of patients with radiation failure have clinically localized disease recurrence, which may be amenable to cure by local salvage therapy, although the burden of co-morbid conditions in this patient population combined with the difficulty and morbidity of local salvage therapies like SRP limit the applicability of these findings. [58]…”
Section: Introductionmentioning
confidence: 99%
“…[567] Furthermore, it has been shown that a high proportion of patients with radiation failure have clinically localized disease recurrence, which may be amenable to cure by local salvage therapy, although the burden of co-morbid conditions in this patient population combined with the difficulty and morbidity of local salvage therapies like SRP limit the applicability of these findings. [58]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation